Head Position and Posturography: A Novel Biomarker to Identify Concussion Sufferers - Frederick Robert Carrick; Guido Pagnacco; Melissa Hunfalvay; Sergio Azzolino; Elena Oggero (Brain Sciences, 2020)
Balance control systems involve complex systems directing muscle activity to prevent internal and external influences that destabilize posture, especially when body positions change. The computerized dynamic posturography stability score has been established to be the most repeatable posturographic measure using variations of the modified Clinical Test of Sensory Integration in Balance (mCTSIB). However, the mCTSIB is a standard group of tests relying largely on eyes-open and -closed standing positions with the head in a neutral position, associated with probability of missing postural instabilities associated with head positions off the neutral plane. Postural stability scores are compromised with changes in head positions after concussion. The position of the head and neck induced by statically maintained head turns is associated with significantly lower stability scores than the standardized head neutral position of the mCTSIB in Post-Concussion Syndrome (PCS) subjects but not in normal healthy controls. This phenomenon may serve as a diagnostic biomarker to differentiate PCS subjects from normal ones as well as serving as a measurement with which to quantify function or the success or failure of a treatment. Head positions off the neutral plane provide novel biomarkers that identify and differentiate subjects suffering from PCS from healthy normal subjects.